Prevention of Firearm Violence Through Specific Types of Community-based Programming: An Eastern Association for the Surgery of Trauma Evidence-based Review. Issue 2 (August 2021) - Bonne, Stephanie L.; Violano, Pina; Duncan, Thomas K.; Pappas, Peter A.; Baltazar, Gerard A.; Dultz, Linda A.; Schroeder, Mary E.; Capella, Jeanette; Hirsh, Michael; Conrad-Schnetz, Kristen; Rattan, Rishi; Como, John J.; et al.
Abstract : Objective: The purpose of this review was to provide an evidence-based recommendation for community-based programs to mitigate gun violence, from the Eastern Association for the Surgery of Trauma (EAST). Summary Background Data: Firearm Injury leads to >40, 000 annual deaths and >115, 000 injuries annually in the United States. Communities have adopted culturally relevant strategies to mitigate gun related injury and death. Two such strategies are gun buyback programs and community-based violence prevention programs. Methods: The Injury Control and Violence Prevention Committee of EAST developed Population, Intervention, Comparator, Outcomes (PICO) questions and performed a comprehensive literature and gray web literature search. Using GRADE methodology, they reviewed and graded the literature and provided consensus recommendations informed by the literature. Results: A total of 19 studies were included for analysis of gun buyback programs. Twenty-six studies were reviewed for analysis for community-based violence prevention programs. Gray literature was added to the discussion of PICO questions from selected websites. A conditional recommendation is made for the implementation of community-based gun buyback programs and a conditional recommendation for community-based violence prevention programs, with special emphasis on cultural appropriateness and community input. Conclusions: Gun violence may be mitigated by community-based efforts, such as gun buybacks or violence prevention programs. These programs come with caveats, notably community cultural relevance and proper support and funding from local leadership. Level of Evidence: Review, Decision, level III. Abstract : Supplemental Digital Content is available in the text